Predisposition of drought occurrence in selected arid areas of the Czech Republic - STŘEDOVÁ, Hana; ROŽNOVSKÝ, Jaroslav; STŘEDA, Tomáš (Contributions to Geophysics and Geodesy, 2013)
Predisposition of drought occurrence is based on combined evaluation of above-normal temperatures and below-normal precipitation. According to the weight of the individual categories of extremity, the five degrees of predisposition to drought were determined (degree 1 is the lowest risk, degree 5 is the highest risk). Evaluation of temperature extremity is based on the determination of abnormality in comparison with average value and standard deviation. Individual categories of extremity of precipitation are determined by comparing the individual monthly data with percentile values. Monthly data of homogenized technical series of the Czech Hydrometeorological Institute were evaluated for the years 1961–2010 in two climatologically dry areas (Břeclav and Kladno county in the Czech Republic). Fourty-two months were rated risky in Břeclav county and fourty-four in Kladno county. The evaluation shows an increase of predisposition to drought, especially after 1990. The highest incidence of degree 5 was recorded in 2001 to 2010 in vegetation season. Subsequently the drought variability as a mean variance of years/season and drought severity as a sum of degree of predisposition to drought of years/season were assessed. A gradual increase of variability and severity from 1961–1970 to 2001–2010 is visible. The lowest values of variability (maximum 2) and severity (maximum 3) in both counties were recorded in winter.